Digital Payment Instruments, Institutional Quality, and Corruption: Evidence from ASEAN - Lak lak Nazhat El Hasanah (Generate Digital Publishing, 2026)
Objective: This study analyzes how digital payment methods, institutional quality, and corruption levels relate in ASEAN countries. It examines how digital payment systems and factors such as the rule of law and regulatory quality affect corruption levels, as measured by the Corruption Perceptions Index (CPI).Research Design & Methods: This study uses a quantitative method called Panel Vector Autoregression (PVAR) to look at how variables relate to each other in panel data. It focuses on five ASEAN countries: Indonesia, Malaysia, Thailand, and Singapore, with data collected from 2010 to 2024.Findings: Research shows that in the short term, only bank credit and the quality of regulation have a significant impact on changes in corruption levels. The formal financial sector and high-quality regulation are important for perceptions of corruption. Digital payment instruments such as ATMs and e-money have a dynamic relationship, but do not have a significant direct impact in the short term.Implications: Research indicates that preventing corruption needs improvements in institutions, regulations, law enforcement, and digitized payment systems. Digital transformation in finance should be combined with institutional reforms to boost transparency, accountability, and integrity in the economy.Contribution & Value Added: This study looks at how digital financial systems, the quality of institutions, and corruption are connected in the ASEAN region. It uses a PVAR approach to analyze both short-term and long-term relationships between these factors. The results aim to show how digital transformation and governance quality can help decrease corruption in developing countries.